Generic Solution Architecture Design of Regulatory Technology (RegTech) - Benny Firmansyah; Arry Akhmad Arman (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2023)
Regulatory Technology, or RegTech, uses new technology that assists the financial industry, such as FinTech and banks, in meeting regulatory compliance. RegTech automates various regulatory compliance activities that were previously manual, such as regulatory interpretation and regulatory reporting, amidst the challenges of the increasing volume of regulations and operational data. Some cutting-edge technologies discovered at RegTech include big data analytics, artificial intelligence, machine learning, robotic process automation, and cloud computing. Although very dominant in the financial industry, RegTech solutions have the potential to be applied in other regulated industries besides finance. Several studies have explored the potential for applying RegTech in industries other than finance, such as charitable organizations, real estate marketplace, pharmaceuticals, and healthcare. Therefore, this study aims to design a generic RegTech solution architecture so that it can be adopted and applied in various regulated industries achieve regulatory compliance more efficiently. Based on the evaluation results, the proposed architecture can be applied in an industrial environment other than financial to be considered generic. Furthermore, an evaluation of the comparison of regulatory compliance business processes without and by implementing RegTech can produce a time efficiency of 95.16%. These results show that RegTech solutions can achieve regulatory compliance more efficiently.